(untitled) (Canadian Medical Education Journal, 2017)
Background: Although students’ transition into medical school is a critical step in their professional journey, orientation has been relatively under-researched, particularly with regard to its intersections with schools’ social missions. This paper reports on a study looking at the implicit messages of orientation to the Northern Ontario School of Medicine’s undergraduate program. Methods: An extended mixed methods study was conducted to look at different aspects of the School’s Orientation Week. The term “hidden curriculum” was used to shape inquiry, both in its broad sense of implicit educational experiences and messages and in its more specific sense of the educational messages sent by a medical school’s culture and activities. Data were collected using participant surveys, focus groups, and interviews. Transcripts and free-text survey responses were analyzed to identify underlying themes. Results: Orientation Week was generally well received and was generally perceived by different stakeholders (such as students, school leaders, and community members) as a positive and necessary undertaking. However, there were points of contention and confusion that created a hidden curriculum with respect to participants’ identities, both as students and as future health professionals. Conclusion: Orientation to undergraduate medical training can be successfully linked to a school’s social mission, but in doing so it can send complex and unintended messages to the participants that may be perceived quite differently based on their circumstances and expectations.